Computational Search to Find Efficient Red/Near‐Infrared Emitting Organic Molecules Based on Thermally Activated Delayed Fluorescence for Organic Light‐Emitting Diodes. Issue 2 (23rd November 2021) - Eskandarian, Parvin; Fallah, Hamidreza; Hajimahmoodzadeh, Morteza; Zabolian, Hossein
Abstract: Computational screening is highly fruitful for initial studies of unknown molecules due to the capability of this tool in molecular discovery and the continuous improvement of computational methods. This article reports how computational studies on more than 300 organic molecules can identify thermally activated delayed fluorescent (TADF) emitters that emit light within the range of red up to near‐infrared (NIR) with high TADF rates. According to time‐dependent density functional theory (TD‐DFT) computations, the best compounds exhibit a low singlet‐triplet energy gap of 0.03 eV and oscillator strength of 0.0425, leading to a high rate of delayed fluorescence decay of 1.4483 μs −1 . Additionally, an experimental‐theory calibration approach is used as an adjunct to experimental research in the future, and emission wavelengths in promising charge‐transfer compounds are estimated as large as 689 nm. Abstract : A library of known molecular materials is computationally screened to find candidates for use as thermally activated delayed emitters in organic light‐emitting diodes. The density functional theory (DFT) and time‐dependent‐DFT calculations identify four red D‐A‐configured molecules with the small singlet‐triplet energy gap (<0.10 eV) and strong oscillator strength of the singlet, and high thermally activated delayed fluorescent rates.